STANISLAS DEHAENE, HOW WE LEARN. THE NEW SCIENCE OF EDUCATION AND THE BRAIN. Great Britain, Penguin Publishing House, 2021, 352 pages, ISBN 978-0-141-98030-3 - Andreea-Diana SCODA (National Centre for Policy and Evaluation in Education, 2022)
Book review